Pengaruh Strategi Event Marketing dan Direct Marketing PT Cyberindo Aditama dalam Meningkatkan Customer Loyalty di Kota Medan - Robbi Pradira Aritonang; Onan Marakali Siregar; Hafiza Adlina (INDO PUBLISHING, 2026)
In the increasingly competitive internet service industry, companies must implement effective marketing strategies to maintain customer loyalty. PT Cyberindo Aditama (CBN), as an internet service provider in Medan, needs to maximize event marketing and direct marketing strategies to build stronger customer engagement. The growing demand for reliable and value-added internet services forms the background of this study. This research aims to analyze the influence of event marketing on customer loyalty, the influence of direct marketing on customer loyalty, and the simultaneous effect of both strategies on CBN customers in Medan. The study focuses on understanding how interactive and personalized marketing activities contribute to enhancing customer loyalty. The research employs a quantitative approach with an associative design. Data were collected through questionnaires distributed to 96 respondents who had subscribed to CBN services for at least six months. Analytical techniques included validity testing, reliability testing, multiple linear regression, t-tests, F-tests, and the coefficient of determination. The results indicate that both event marketing and direct marketing positively and significantly influence customer loyalty. Simultaneously, these variables also show a significant effect, with an R Square value of 0.568, meaning that 56.8% of customer loyalty variation is explained by the two marketing strategies, while the remaining 43.2% is influenced by other factors outside the model. These findings confirm that event marketing and direct marketing are essential instruments in strengthening customer loyalty toward CBN in Medan.